Development of Contextual-Based E-Comic Learning Media to Improve Students' Critical Thinking Skills in Plantation Areas - Wicaksono, Iwan; Husni Farros , Muhammad; Mohd Salleh, Sallimah; Chin Chen, Yong; Nuha, Ulin (Universitas Negeri Surabaya, 2025)
Objective: Critical thinking skills are a crucial component of education. However, in the context of education in Indonesia, the development of critical thinking skills has not yet reached the expected level. The low level of students' critical thinking skills is due to the limited use of innovative learning media in science education at school. One potential solution is the use of contextual-based e-comics. This study aims to evaluate the validity, practicality, and effectiveness of contextual-based e-comic products. Method: The research employed a Research and Development (R&D) approach using the ADDIE model. Results: The validity of the contextual-based e-comics received an average score of 90%, placing it in the very valid category. The practicality score averaged 89%, categorized as very practical. The effectiveness measured by an average N-Gain of 0.70, falls into the high category with a student response rate of 95% and classified as very good. Novelty: This study introduces an innovation in learning media by developing e-comics that integrate a contextual approach to improve junior high school students’ critical thinking skills in plantation areas. The selection of plantation areas adds a novel aspect and differentiates this study from previous studies, aiming specifically to improve critical thinking skills of junior high school students in plantation areas.